CREATIVE TRAINING IN BUSINESS SCHOOLS - Ortiz Esaine, Nicolás (2016)
This article deals with the importance of developing creative competencies in business sciences professionals, specifically marketing. It seeks to show the scope and advantages found in the development of lateral thinking so as to achieve a more empathetic relationship between business managers and their target audiences within a globalized economic context requiring greater personalization and social emphasis on corporate actions. This all is addressed from the parallel experience in creative and business schools, with the new approaches in business planning based on lateral, iterative, and cooperative thinking exercises as a starting point, and existing innovations as an example. The goal is to generate model proposals that can be integrated into the curriculums, and can shorten the gaps expressed today by independent business schools as opposed to the typical university academic model, and also to provide for the generational gaps existing in new consumers.